Perbedaan Self Confidence Siswa antara Creative Problem Solving dan Discovery Learning Ditinjau dari Gender - Ahmad Isnaini; Edy Surya (Idealmathedu: Indonesian Digital Journal of Mathematics and Education, 2019)
This study aims to see the differences in students' self confidence between students with the treatment of the creative problem solving learning model and the discovery learning model analysed based on gender. The data analysis was done using two-way Anava with different number of cell to see the effect of gender and learning models on students' self confidence. After the effect of gender and the learning model was found, a further post-Anova test using Scheffe method was executed. This analysis shows the following results: gender has an influence on students' self confidence as well as there is an influence of the learning model on students' self confidence, there is no interaction between gender and learning models on students' self confidence. When a post-Anova test with Scheffe's method was applied, it is found that there are differences in students' self confidence between the creative problem solving model and the discovery learning model. Female students have better self confidence than male students , while the creative problem solving model provides better self confidence than discovery learning model.